Syndecan-1 Amplifies Ovalbumin-Induced Airway Remodeling by Strengthening TGFβ1/Smad3 Action - Zhang, Dong; Qiao, Xin-rui; Cui, Wen-Jing; Zhang, Jin-tao; Pan, Yun; Liu, Xiao-fei; Dong, Liang (Frontiers in Immunology, 2021)
Syndecan-1 (SDC-1) is a transmembrane proteoglycan of heparin sulfate that can regulate various cell signal transduction pathways in the airway epithelial cells and fibroblasts. Airway epithelial cells and human bronchial fibroblasts are crucial in airway remodeling. However, the importance of SDC-1 in the remodeling of asthmatic airways has not been confirmed yet. The present study was the first to uncover SDC-1 overexpression in the airways of humans and mice with chronic asthma. This study also validated that an increase in SDC-1 expression was correlated with TGFβ1/Smad3-mediated airway remodeling in vivo and in vitro. A small interfering RNA targeting SDC-1 (SDC-1 siRNA) and homo-SDC-1 in pcDNA3.1 (pc-SDC-1) was designed to assess the effects of SDC-1 on TGFβ1/Smad3-mediated collagen I expression in Beas-2B (airway epithelial cells) and HLF-1 (fibroblasts) cells. Downregulation of the SDC-1 expression by SDC-1 siRNA remarkably attenuated TGFβ1-induced p-Smad3 levels and collagen I expression in Beas-2B and HLF-1 cells. In addition, SDC-1 overexpression with pc-SDC-1 enhanced TGFβ1-induced p-Smad3 level and collagen I expression in Beas-2B and HLF-1 cells. Furthermore, the levels of p-Smad3 and collagen I induced by TGFβ1 were slightly increased after the addition of the recombinant human SDC-1 protein to Beas-2B and HLF-1 cells. These findings in vitro were also confirmed in a mouse model. A short hairpin RNA targeting SDC-1 (SDC-1 shRNA) to interfere with SDC-1 expression considerably reduced the levels of p-Smad3 and remodeling protein (α-SMA, collagen I) in the airways induced by ovalbumin (OVA). Similarly, OVA-induced p-Smad3 and remodeling protein levels in airways increased after mice inhalation with the recombinant mouse SDC-1 protein. These results suggested that SDC-1 of airway epithelial cells and fibroblasts plays a key role in the development of airway remodeling in OVA-induced chronic asthma.